IMPLEMENTASI KEBIJAKAN PENGELOLAAN AIR LIMBAH PADA INDUSTRI BATIK DI DESA SAMBOREJO, KABUPATEN PEKALONGAN - Tsania Zahra Haniza; Nina Widowati; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2022)
The Pekalongan Regency Government has attempted to deal with the issue of batik industry wastewater pollution by issuing Pekalongan Regency Regional Regulation Number 5 of 2014 concerning Wastewater Management. The purpose of this study was to analyze the implementation of policies and identify the driving and inhibiting factors in the implementation of Wastewater Management policies in the batik industry in Samborejo Village, Pekalongan Regency. This study uses a qualitative descriptive method with data collection techniques through interviews and documentation. The results showed that the batik industry players in Samborejo Village had not fulfilled several obligations and did not have a waste water disposal permit that had been stipulated in the policies, guidance and supervision of batik industry players in Samborejo Village had not been carried out strictly, and the Pekalongan Regency Government had not been able to provide Strict sanctions to the batik industry players in Samborejo Village who commit violations. The inhibiting factors include, there are standards and objectives of policy implementation that have not been achieved, limited budgetary resources, communication between the Pekalongan Regency Government and batik industry players in Samborejo Village that is not sustainable, supervision activities have not been carried out strictly, and unfavorable socio-economic conditions.